Conferencia organizada por las JJ.LL. de la barricada de La Torrasa a cargo de Manuel Perez. Perez speaks. Series of 3 photos. Copied from CNT collection
Conferencia organizada por las JJ.LL. de la barricada de La Torrasa a cargo de Manuel Perez. Perez speaks. Series of 3 photos. Copied from CNT collection.